THE UTILIZATION OF SHELLS AS A BASIC MATERIAL FOR MAKING CHALK PAINT IN GAMPONG KUALA LANGSA - Rini Fitriani; Zulfiani; Ellida Novita Lydia (Global Science Society, 2021)
Gampong Kuala Langsa West Langsa subdistrict is a coastal area where the people mostly live fishermen's livelihoods. The natural wealth produced by the community is one of the sea shells, where the shells are usually sold already in a peeled state that leaves the shell waste that accumulates. Shell waste is not used by the community into something that has value because there is no driver, for that the Community Service Team (PKM) socializes to the community so that the shell waste has economic value and can be utilized by the Gampong Kuala Langsa community and can also be marketed around Langsa City, namely in the form of making paints whose raw materials from shell waste can be used. The resulting wall paint is a natural and environmentally friendly wall paint. In addition, the resulting paint has the same value or quality as the paint sold in the market.